Toxicity profile of chemotherapy agents used in cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for peritoneal surface malignancies. Issue 4 (April 2020) - Somashekhar, S.P.; Yethadka, Ramya; Kumar C, Rohit; Ashwin, K.R.; Zaveri, Shabber; Rauthan, Amit
Abstract: Introduction: Morbidity associated with cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is due to the synergistic effect of cytoreduction, effect hyperthermia and the cytotoxic agents used for HIPEC. This study was done to analyse the postoperative morbidity in relation to the chemotherapy agent used in patients undergoing CRS-HIPEC for peritoneal surface malignancy (PSM) in Indian set up. Materials and methods: Patient with PSM, underwent CRS-HIPEC as per the institutional protocol. Patients were stratified as per the chemotherapy drug used during HIPEC & perioperative outcome were documented. Results: 163 patients underwent CRS-HIPEC for PSM: 67.4% were of ovarian primary. Others were colorectal, appendicular, gastric primary and rare tumors.Cisplatin was the most common drug used: as alone (57.05%) or in combination with Adriamycin (12.88%). Mitomycin-C (MMC) was used in 20% and oxaliplatin in 10%.Grade 3–5 morbidity in the whole cohort was 44.8% and grade 1–2 was 74%.Grade 1–2 electrolyte abnormality was the most common morbidity overall and grade 3–4 hematological toxicity was the most common severe morbidity. Frequency of grade 3–5 morbidity were 38.7%, 48.5%, 50% and 61.9% for Cisplatin alone, MMC, oxaliplatin and Adriamycin + cisplatin respectively. None of the patients had grade 3–4 nephrotoxicity as sole complication. All major complications were highest in the group who received Adriamycin. Cisplatin was associated with higher rate of electrolyte imbalance, oxaliplatin with post-operative bleeding. Rates of other complications did not differ significantly. Conclusion: Cisplatin followed by MMC were the well tolerated drugs during HIPEC and tolerance to Adriamycin combination regimen in Indian patients was poor.